(untitled) (Research, Society and Development, 2022)
Red biopigments produced by actinobacteria represent an important substitute in the food industry to synthetic pigments, which can cause harmful effects on human health and the environment. In this study, pigment production by actinobacteria strain UFPEDA 3422, identified by polyphasic taxonomy, was investigated. The cultivation parameters related to growth and pigment production were assayed in solid culture media and submerged fermentation. The red cell pigment was extracted with ethyl acetate and analyzed in a UV-Vis spectrophotometer with maximum production of the pigment (34.9 AU540 nm) in Hickey-Tresner (HT) medium for 48 hours at 37 ºC. The maximum biomass concentration (33.4 g/L) was obtained after 96 hours. Polyphasic taxonomy confirms 97.4% similarity of strain UFPEDA 3422 with the Amycolatopsis, a rare genus able to produce pigments on different substrates. In addition, the microorganism has tolerance to temperature variations, pH fluctuations and concentrations of 5% NaCl. The determination of cultivation and pigment production parameters show the potential of Amycolatopsis sp. as an alternative source of natural pigments.